The association between adolescents’ independent food purchasing and dietary quality differs by socioeconomic status: Findings from a pilot study - Sarah Shaw; Sarah Crozier; Cyrus Cooper; Dianna Smith; Mary Barker; Christina Vogel (PLoS ONE, 2025)
During adolescence, many young people start to make more independent food purchases. Subsequently, these independent food choices will increasingly contribute to their overall diet quality; little is known, however, about this relationship. This pilot study aimed to examine the role adolescents’ independent food purchases play in their diet quality and assess if these relationships vary according to socio-economic status. A convenience sample of adolescents aged 11–18 years and attending secondary school or college in Hampshire, England, were recruited to participate in a one-week cross-sectional observational study. A validated 20-item Food Frequency Questionnaire assessed diet quality. Participants used an ecological momentary assessment mobile phone app to record food purchases. Over seven days, 552 food/drink items were purchased on 253 food purchasing occasions by 80 participants. The majority of purchases (n = 329, 59%) were coded as ‘not adhering’ to the UK Eatwell Guide, 32% were coded as ‘adhering’ and 9% fell between these categories being coded as ‘combination’. The healthfulness of food purchases did not differ between adolescents from low- and high-SES households. Across all adolescents, 39% reported that their food and drink purchases were snacks and these were less healthful than purchases made for main meals. Fully adjusted regression models showed that adolescents who made less healthy food purchases tended to have poorer quality diets (β 0.36, (95%CI −0.15, 0.87) p = 0.16). Interaction models showed that less healthy purchasing was more strongly associated with poorer diet quality among young people of lower SES than those of higher SES (p = 0.01). Future research should focus on identifying ways to support more healthful independent food choices by adolescents to reduce dietary inequalities and improve health and well-being among the next generation of adults.